What Kinds of Jobs Help Carers Combine Care and Employment? - Griffiths, M; Thomson, C; Hill, T; Bittman, M (My University, 2008)
This paper provides information about what job characteristics promote or inhibit maintaining employment while caring. Using a nationally representative longitudinal data set - the Household Income and Labour Dynamics in Australia (HILDA) survey - the paper traces the effects of the onset of care on labour force participation. This study used multivariate techniques to analyse five clusters of influences that might affect carer employment: the intensity of care responsibilities; the employees' own characteristics; the characteristics of their employment; their workplace arrangements; and the employee's rating of the stress, satisfaction and security associated with their job. The results showed that moderate to intensive caring responsibilities militate against maintaining labour force participation in the face of caring responsibility. Working as a casual employee, in a job without supervisory responsibilities, in smaller firms, with poor leave arrangements, no flexibility in hours and low job security all decrease the probability that carers remain in employment.
Family Matters
Keywords: Carers -- Employment; Carers; Labour market; Carers; Employment; Employment and unemployment